Marketing of Multipurpose Tree Produce in the Tropics - Hegde, N. G. (Indian Forester, 1999)
Cultivation of Multi-Purpose Tree Species (MPTS) by farmers, collection of the produce and marketing it for income generation has been described. To organise the market, these species should be divided into wood and non-wood and products handled appropraitely.